Implementation of E-Government in Regional Asset Management at The Regional Financial and Asset Management Agency in Serang City - Nurul Inayah (Epistemik Press, 2023)
E-Government is an effort to develop a good government system based on electronics. E-Government is expected to encourage all government institutions from central to local to utilize ICT. BPKAD (Regional Financial and Asset Management Agency) of Serang City is one of the agencies that has implemented e-government in each of their activities. However, in its implementation there are still obstacles that result in not running optimally about the implementation of e-government in BPKAD Serang City. The purpose of this research is to find out and analyze what the implementation of e- government in asset management using ATISISBADA (Regional Goods Cycle Information Technology Application) is like at BPKAD Serang City. This research uses Indrajit’s e-government Implementation theory. The research method used is a descriptive method with a qualitative approach. Because the main purpose of this research is to provide a description and explanation related to the implementation of e- government, especially in the ATISISBADA application properly and correctly. Informants of this research are employees in BPKAD, especially the assets section who manage ATISISBADA. Data collection techniques carried out by observation, interviews, documentation and literature study with data obtained 2, primary data and secondary data. From this research it can be concluded that the application of e-government in asset management using ATISISBADA still has obstacles in terms of human resources, then the application and internet network are still experiencing problems, resulting in the process of implementing e-government in BPKAD Serang City not running optimally.